Intravenous administration of activated protein C in Pseudomonas-induced lung injury: impact on lung fluid balance and the inflammatory response - Fourrier François; Nevière Rémi; Prangère Thierry; Tournoys Antoine; Collet François; Robriquet Laurent; Guery Benoît P (Respiratory Research, 2006)
Abstract Background Acute lung injury (ALI) induces a coagulation/fibrinolysis imbalance and leads to fibrin deposition. The protein C pathway is an important regulator of the coagulation system and reduces the inflammatory response. The aim of the study was to examine the effects of recombinant human activated protein C (rhAPC) in the early phase of Pseudomonas aeruginosa (Pa)-induced lung injury. Methods The study was conducted in vivo on a rat model of Pa-induced ALI. Continuous intravenous (IV) rhAPC was administrated simultaneously with intratracheal (IT) Pa. We instilled into the airspaces a 5% bovine albumin solution with 1 μ(Ci of 125 I-albumin and injected IV 1 μ(Ci of 111In-albumin to measure lung liquid clearance (LLC) and endothelial injury. Cytokines levels (TNFα and IL-6) and thrombin-antithrombin (TAT) complexes were measured in blood and bronchoalveolar lavage fluid (BALF) at 4 hours. Four groups were compared: control (CTR), pneumonia (PNP) receiving IT Pa (0.5 ml/kg of 1 × 109 cfu), APC: IV rhAPC (300 μg/kg/h), A-PNP: IT Pa /IV rhAPC. Results Alveolar-capillary permeability was increased in the PNP versus the CTR group (0.28 ± 0.08 vs. 0.03 ± 0.01, p < 0.05). IV rhAPC in Pa-induced ALI led to further injury (0.47 ± 0.17 vs. 0.28 ± 0.08, p = 0.2). The LLC was significantly decreased in the A-PNP group compared to PNP group (9.1 ± (4.3% vs. 33.4 ± 2.6%, p < 0.05). The lung wet to dry weight ratio was significantly increased in the PNP group (4.62 ± 0.31) compared to the CTR group (3.87 ± 0.22, p < 0.05). IV rhAPC administration tends to increase this parameter in Pa-induced ALI (5.80 ± 0.66, p = 0.07). These findings were associated with a loss of inflammatory response compartmentalization measured by TNFα and IL-6 systemic levels. TAT complexes in BALF were increased in the A-PNP group (23.17 ± 2.89 ng/ml) compared to the CTR group (0.92 ± 0.17 ng/ml, p < 0.05) and the PNP group (11.06 ± 2.76 ng/ml, p < 0.05). Conclusion rhAPC reduces LLC following Pa-induced ALI and may influence pulmonary edema formation. The early massive fibrin formation is probably beneficial in ALI limiting both the extent of injury and permeability disorders.